MAKNA KASIH DALAM KOMPOSISI “UNA LIMOSNA POR EL AMOR DE DIOS” KARYA AGUSIN BARRIOS MANGORE - Recky Rusman; Meyltsan Herbert Maragani (Clef: Jurnal Musik dan Pendidikan Musik, 2020)
Abstract This research aims to describe the meaning of love in the composition "Una Limosnita Por El Amor de Dios" by Agustin Barrios Mangore. The method used in this research is a qualitative method with a qualitative descriptive approach. Based on the results of the analysis and interpretation of the data, an indication that the meaning of love from the composition "Una Limosnita Por El Amor de Dios" is reflected in the title and musical elements in the composition. The title of the song, which means "Charity for the Love of God" has the meaning of living in loving one another (Philia's love) to reflect God's love (Agape love). The elements that support the delivery of meaning in the composition of the song Una Limosnita Por El Amor de Dios are the use of minor scales and modulation to major notes, stepping melody intervals, tremolo ornaments throughout the song, intros which are accompaniment motifs along the song, there are along Picardy at the end of the repetition of the theme, the use of the plot is diminished before the major line at the end of the song, the dynamics that are played are based on the feelings of the player.